Integrating a Social Justice Perspective in Economics Education: Creating a Distinctly Catholic Education - Carrithers, David F.; Peterson, Dean (Catholic Education: A Journal of Inquiry and Practice, 2010)
This paper suggests a way of creating a distinctly Catholic economics education by integrating a social justice perspective into the curriculum through writings from Catholic Social Thought (CST). In so doing, we argue that students of economics will gain a more thorough understanding of the economics discipline. Moreover, a grounding in CST will help business and economics students better negotiate the conflicting view of markets they encounter in the “disconnect” between business courses and humanities/social science core courses. The thesis of the paper is that CST can be a useful mechanism by which to instill a social justice perspective in economics education and to motivate educators to be clear and complete in discussing assumptions that underlie economic theory. We explore reasons economics educators have been reluctant to use tools such as CST to inform their discussion of economic theory. We use the subdiscipline of welfare theory and in particular assumptions regarding the common good, preference satisfaction, and individual and social utility to distinguish between perspectives from CST and what is taught as modern economic theory. Finally we offer some simple curricular changes that can be accomplished with little cost, which can lead to three bold accomplishments: creating a distinctly Catholic economics education, improving students’ understanding of their discipline, and diminishing the frustration and confusion students feel when they encounter disconnected messages about the effects of markets and the promotion of social justice.